Insecticidal effects of selected plant extracts on rice weevil, Sitophilus oryzae L. and rice moth, Corcyra cephalonica (St) - Khani, Mousa (2012)
The present study was conducted with the objectives of extraction and evaluation the of chemical constituents from black pepper (Piper nigrum L.), peppermint (Mentha piperita L.), and physic nut (Jatropha curcas L.), and to investigate effects of these plant extracts on toxicity, mortality, repellency, antifeedant activity, egg hatchability and adult emergence of the rice weevil and rice moth under laboratory conditions. Crude extracts were prepared by percolation method and essential oils were prepared by hydro distillation method. Among the nine extracts screened for toxicity, petroleum ether and chloroform extract of P. nigrum and petroleum ether extract of J. curcas showed significant insecticidal potential. The LC50 values of the above extracts against S. oryzae adults were 1.61, 1.70 and 6.82 µL/mL, and against C. cephalonica larvae were 12.52, 14.31 and 13.22 µL/mL, respectively. The LC50 values of M. piperita and P. nigrum essential oils against adults of S. oryzae were 85.0 and 288.8 µL/L air, and against C. cephalonica larvae were 343.9 and 530.5 µL/L air, respectively. The GC and GC-MS analysis showed that the major components of P. nigrum extracts were piperine (75.5%) and caryophyllene (18.5%). The major components of J. curcas seed oil were oleic acid (40.7%), linoleic acid (34.2%) and palmitic acid (18.0%). GC-MS analysis also showed that the major components of M. piperita essential oils were menthol (47.0%), isomenthone (19.9%), limonene (7.5%) and cineole (5.4%), while the major components of P. nigrum essential oils were limonene (33.8%),@-pinene (31.2%) and !-pinene (23.3%). Mentha piperita and P. nigrum essential oils showed significant effectiveness against adults of S. oryzae and C. cephalonica larvae compared to the control. Mentha piperita oil strongly inhibited feeding in S. oryzae compared to P. nigrum essential oils, but there was an inverse effect on repellency activity. Essential oils of both plant species showed no repellency activity against 3rd instar larvae of C. cephalonica. However, M. piperita essential oils strongly inhibited egg hatchability in S. oryzae as compared to P. nigrum essential oils. Also M. piperita essential oils had a stronger inhibitory activity on adult emergence than P. nigrum essential oils in both insect species. Nutritional bioassay revealed significant reduction in the relative growth rate (RGR),relative consumption rate (RCR) and food utilization (ECI) by rice weevil and rice moth at concentration range between 2 - 10 µL/g of rice kernels with feeding deterrence indices (FDI) reaching 43.5 and 74.9%, respectively. The plant oils also showed repellency activity against adults of S. oryzae, while, there was no repellency activity against 3rd instar larvae of C. cephalonica. The plant extracts when applied on rice kernels against adults of S. oryzae at concentrations of 0.5 -2 µL/mL, and C. cephalonica larvae at 2-10 µL/mL, resulted in significant (P < 0.05) reductions in egg hatchability. Adult emergence was also drastically reduced by P. nigrum and J.curcas extracts when applied to rice kernels. The plant extracts strongly suppressed adult emergence of both insects at equivalent dose levels. The results revealed significant insecticidal effects of the selected plant extracts. There is therefore immense potential for development of novel insecticides from these plant species.